Pengembangan Bahan Ajar Berbasis Discovery Learning (DL) pada Pembelajaran IPAS untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik Kelas VI Sekolah Dasar - Ook Aven Agusta; Endang Widi Winarni; Neza Agusdianita (UNIB Press, 2026)
The purpose of this study was to develop Discovery Learning (DL)-based teaching materials for science learning to improve the cognitive learning outcomes of sixth-grade elementary school students. The type of research employed was Research and Development (R&D) using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Both quantitative and qualitative data were collected. Quantitative data were obtained from validation results by material, language, and graphics experts, product trials, and effectiveness tests through pretests and posttests. Qualitative data were obtained from interviews, observations, and questionnaires regarding teacher and student responses. The results of the study indicate that the Discovery Learning (DL)-based teaching materials developed were declared suitable for use according to the validators from material, language, and graphics experts. Teacher and student responses were categorized as very positive regarding the appearance and ease of use of the materials. In addition, the effectiveness test results showed an increase in students' cognitive learning outcomes with an N-Gain Score of 0.7328, which falls into the fairly effective category. Based on these results, it can be concluded that Discovery Learning (DL)-based teaching materials are quite effective in improving the cognitive learning outcomes of sixth-grade elementary school students.